Pricing to Market, Staggered Contracts, and Real Exchange Rate Persistence - Robert Feenstra; Paul Bergin (University of California, Department of Economics, 1999)
This paper offers an explanation for the persistence observed in real exchange rate movements. The model combines pricing to market behavior with sticky prices generated by staggered contracts. A translog preference structure is used to enhance both features. The paper finds that openness limits the degree of endogenous persistence. Nevertheless, the model under reasonable parameter values can replicate the serial correlation of real exchange rate data. Further, significant exchange rate volatility can be generated, and this is amplified by the presence of endogenous persistence.
Keywords: 330